PSYCHOLOGICAL „CONCEPTION” POLITICAL PROGRAMMING TV - Головчук, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Television peculiar to certain psychological effect of X-ray that can open the viewer superficial layers of the human „I". And the presence of these abilities television shows mainly its strengths – a special power to call upon conviction. This feature television media has always used the power, you could even say that the facts are not unusual manipulation of mass consciousness in the worst sense. Therefore, the psychological aspects of television programming concepts is the object of study of contemporary political scientists, sociologists, and most TV. Today is a particularly acute danger of standardizing the individual posed television.